Metal concentrations in Bukit Merah Lake, Perak - M. Shuhaimi-Othman,; A.K. Ahmad,; G. Norziana, (Universiti Kebangsaan Malaysia, 2010)
Study on metal concentrations in water of Bukit Merah Lake was conducted in April 2009. Fifteen sampling stations were chosen and surface water samples for metals determination were collected. Some water quality parameters such as temperature, conductivity, dissolved oxygen, pH, and water hardness were determined at each station. Eleven metals i.e. cadmium, zinc, lead, copper, nickel, ion, cobalt, aluminium, barium, cromium dan manganese were determined in water samples. Results show that in general metals concentration were lower than maximum concentrations allowed by Malaysian and international standards in protecting aquatic life except for Fe and Al. For water quality parameters, study showed that all parameters are in natural concentration range (class I) according to National Water Quality Standard (NWQS Malaysia) except for dissolved oxygen and pH at some sampling stations especially at east side of the lake which were influenced by natural and anthropogenic factors.